Key challenges of health care workers in implementing the integrated management of childhood illnesses (IMCI) program: a scoping review - Reñosa, Mark Donald; Dalglish, Sarah L.; Bärnighausen, Kate; McMahon-Rössle, Shannon A. (Global health action, 2020)
Background: Several evaluative studies demonstrate that a well-coordinated Integrated Management of Childhood Illnesses (IMCI) program can reduce child mortality. However, there is dearth of information on how frontline providers perceive IMCI and how, in their view, the program is implemented and how it could be refined and revitalized.Purpose: To determine the key challenges affecting IMCI implementation from the perspective of health care workers (HCWs) in primary health care facilities.Methods: A scoping review based on the five-step framework of Arskey and O’Malley was utilized to identify key challenges faced by HCWs implementing the IMCI program in primary health care facilities. A comprehensive search of peer-reviewed literature through PubMed, ScienceDirect, EBSCOhost and Google Scholar was conducted. A total of 1,475 publications were screened for eligibility and 41 publications identified for full-text evaluation. Twenty-four (24) published articles met our inclusion criteria, and were investigated to tease out common themes related to challenges of HCWs in terms of implementing the IMCI program.Results: Four key challenges emerged from our analysis: 1) Insufficient financial resources to fund program activities, 2) Lack of training, mentoring and supervision from the tertiary level, 3) Length of time required for effective and meaningful IMCI consultations conflicts with competing demands and 4) Lack of planning and coordination between policy makers and implementers resulting in ambiguity of roles and accountability. Although the IMCI program can provide substantial benefits, more information is still needed regarding implementation processes and acceptability in primary health care settings.Conclusion: Recognizing and understanding insights of those enacting health programs such as IMCI can spark meaningful strategic recommendations to improve IMCI program effectiveness. This review suggests four domains that merit consideration in the context of efforts to scale and expand IMCI programs.